Uji Ketahanan Planlet Anggrek Bulan (Phalaenopsis amabilis (L.) Bl.) Hasil Seleksi dengan Asam Salisilat Terhadap Fusarium oxysporum Secara In Vitro - Ria Aulia Noviantia; Endang Nurcahyani; Martha Lulus Lande (Politeknik Negeri Lampung., 2017)
Phalaenopsis amabilis cultivated have many constraints such as the appearance of fusarium wilt disease caused by Fusarium oxysporum. Plantlet P.amabilis which resistant to F. Oxysporum was selected in the solid Vacin and Went (VW) medium was added with salicylic acid at concentrations of 65 ppm, 75 ppm, and 85 ppm, compared with controls (0 ppm). The goals of the research were to study and determine of: 1) The SA concentration of planlet P. amabilis selection tolerant; 2) The proper concentration of AS during in vitro selection for suppressing the Fo. The research was carried out in December 2015 to February 2016 in the Botany Laboratory (in vitro research room), Departement of Biology, Faculty of MIPA, Lampung University. The result showed that: 1) The SA tolerant concentration for plantlet selection with P. amabilis was between 65 ppm - 85 ppm. 2) The 85 ppm of SA was effective for suppressing the Fo compared to 65 ppm and 75 ppm. Keywords: Phalaenopsis amabilis, salicylic acid, Fusarium oxysporum, In vitro, Resistance.